Aging and Health Policies in Chile: New Agendas for Research. Issue 4 (2nd October 2017) - Thumala, Daniela; Kennedy, Brian K.; Calvo, Esteban; Gonzalez-Billault, Christian; Zitko, Pedro; Lillo, Patricia; Villagra, Roque; Ibáñez, Agustín; Assar, Rodrigo; Andrade, Maricarmen; Slachevsky, Andrea
Abstract : Abstract —Population aging is among the most important global transformations. Compared to European and North American countries, Chile is among the countries with the fastest growth of life expectancy at birth during recent decades. The aging of Chile's population is related to the improvement of living conditions, but also entails risks that tend to be associated with a rapid economic growth accompanied by large income inequalities and a chronic deficit of basic social benefits. The rapid demographic transition towards an aged population has unfolded in a context of poor development of public policies to tackle the opportunities and needs associated with an aging society. This article provides a brief overview of current Chilean public policy on aging, with a focus on healthy aging as defined by World Health Organization. The discussion addresses core challenges to successfully achieve healthy aging in Chile.